Evaluation of nurses' practices related to personal protective equipment Regarding Preventive Measures of Transmission of COVID-19 in Baghdad Teaching Hospital (Texas Journal of Multidisciplinary Studies, 2022)
This study aim to evaluate of nurses' practices related to personal protective equipment Regarding Preventive Measures of Transmission of COVID-19, A cross-sectional study design is carried out , A non – probability (purposive) sample of (60) nurses (males and females), who were working in Baghdad Teaching Hospital from different units. The result showed that nurses have low level of practices i all items related to personal protective equipment Regarding Preventive Measures of Transmission of COVID-19. This study recommended of the Ministry of Health to increase the number of training courses regarding COVID-19 across Iraq to keep and enhance the practice about COVID-19.